FAKTOR YANG MEMENGARUHI KEJADIAN DERMATITIS PADA SANTRI DI PESANTREN MODERN AL MUKHLISHIN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2014 - Meutia Nanda, SKM., M.Kes (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2017)
ABSTRACT      Skin disease is one disease that is still a public health problem in Indonesia. Dermatitis is inflammation of the skin (epidermis and dermis) as a response to the influence of exogenous factors and endogenous factors and complaints or itchy places like dormitories populous and humid places and lack of sunshine a major factor in the spread of skin diseases. One of the places that are at high risk of developing this disease is a boarding school. This type of observational analytic study with cross-sectional research design to analyze the influence of the factors influencing the incidence of dermatitis in children boarding students Al Mukhlishin Tanjung Morawa. Data Analysis with Chi Square and logistic regression.  Expected the students to be able to keep his own personal hygiene such as bathing twice a day, not an exchange of towels, no exchange of clothes, changing, washing bedding once a week and to avoid moisture drying mattress   Keywords: Dermatitis, Length of Stay, Health Towel, Health Beds